Perlindungan Hukum terhadap Hak Mutlak (Legitime Portie) Ahli Waris Golongan I dalam Sengketa Wasiat (Studi Analisis Putusan Nomor 345/Pdt.G/2025/PN Jkt.Pst) - Rayi Kharisma Rajib; Anggun Lestari; Novita Eka Wardhani (CV. ITTC INDONESIA, 2026)
This research analyzes the legal protection of the absolute right (Legitime Portie) of Category I heirs in inheritance disputes, focusing on Court Decision Number 345/Pdt.G/2025/PN Jkt.Pst. The primary issue examined is the tension between the principle of freedom of testation (testamentaire vrijheid) and the legal obligation to protect the rights of forced heirs (legitimaris) under Article 913 of the Indonesian Civil Code (KUHPerdata). The research method employed is normative legal research using statutory, conceptual, and case approaches. The results indicate that biological children, as Category I heirs, hold the status of legitimacy who are entitled to a minimum portion of the inheritance that cannot be eliminated by the testator. In the analyzed decision, the Panel of Judges rejected the annulment of the will deed because the plaintiff failed to overturn the perfect evidentiary strength of the authentic deed. The judges reasoned that the application of the substitution vulgaris doctrine in the will did not directly violate the absolute right but merely postponed its execution to ensure the welfare of the surviving spouse. The protection of the absolute right is implemented through the recognition of the plaintiff's legal status as a legitimate heir, even though the execution of their economic rights is subject to the gradual distribution mechanism regulated in the will.